Gauging the laboratory responses to coronavirus disease (Covid-19) in Africa - Festus A. Odeyemi; Ibrahim A. Adekunle; Olakitan W. Ogunbanjo; Jamiu B. Folorunso; Thompson Akinbolaji; Idowu B. Olawoye (African Governance and Development Institute (AGDI), 2020)
The rampaging effect of coronavirus disease (COVID-19) in Africa is huge and have impacted almost every area of life. Across African states, there exist variations in the laboratory measures adopted, and these heterogeneous approaches, in turn, determines the successes or otherwise recorded. In this study, we assessed the various forms of laboratory responses to the containment, risk analyses, structures and features of COVID-19 in high incidence African countries (Nigeria, South Africa, Egypt, Ghana, Algeria, Morocco, etc.) to aid better and efficient laboratory responses to the highly infectious diseases.
Keywords: 330; Laboratory responses; COVID-19; PCR; Sample Pooling; Africa